Exploring variation of coverage and access to dental care for adults in 11 European countries: a vignette approach - Winkelmann, Juliane; Gómez Rossi, Jesús; Schwendicke, Falk; Dimova, Antoniya; Atanasova, Elka; Habicht, Triin; Kasekamp, Kaija; Gandré, Coralie; Or, Zeynep; McAuliffe, Úna; Murauskiene, Liubove; Kroneman, Madelon; et al. (BMC oral health, 2022)
BACKGROUND: Oral health, coupled with rising awareness on the impact that limited dental care coverage has on oral health and general health and well-being, has received increased attention over the past few years. The purpose of the study was to compare the statutory coverage and access to dental care for adult services in 11 European countries using a vignette approach. METHODS: We used three patient vignettes to highlight the differences of the dimensions of coverage and access to dental care (coverage, cost-sharing and accessibility). The three vignettes describe typical care pathways for patients with the most common oral health conditions (caries, periodontal disease, edentulism). The vignettes were completed by health services researchers knowledgeable on dental care, dentists, or teams consisting of a health systems expert working together with dental specialists. RESULTS: Completed vignettes were received from 11 countries: Bulgaria, Estonia, France, Germany, Republic of Ireland (Ireland), Lithuania, the Netherlands, Poland, Portugal, Slovakia and Sweden. While emergency dental care, tooth extraction and restorative care for acute pain due to carious lesions are covered in most responding countries, root canal treatment, periodontal care and prosthetic restoration often require cost-sharing or are entirely excluded from the benefit basket. Regular dental visits are also limited to one visit per year in many countries. Beyond financial barriers due to out-of-pocket payments, patients may experience very different physical barriers to accessing dental care. The limited availability of contracted dentists (especially in rural areas) and the unequal distribution and lack of specialised dentists are major access barriers to public dental care. CONCLUSIONS: According to the results, statutory coverage of dental care varies across European countries, while access barriers are largely similar. Many dental services require substantial cost-sharing in most countries, leading to high out-of-pocket spending. Socioeconomic status is thus a main determinant for access to dental care, but other factors such as geography, age and comorbidities can also inhibit access and affect outcomes. Moreover, coverage in most oral health systems is targeted at treatment and less at preventative oral health care.
Keywords: Health Services Accessibility; Evropa; stomatologická péče; orální zdraví; výdaje na zdravotnictví; lidé; Health Services; Adult; Europe; Health Expenditures; Dental Care; zdravotnické služby; dospělí; Humans; dostupnost zdravotnických služeb; Oral Health